Necesidad de crear un sistema de control eficaz, garantizado para lograr el cumplimiento de las obras contratadas por el estado en el tiempo previsto. - Chamba Rodriguez, Melki Manuel (2012)
The logic teaches us that the existent thing should be known for of there to project the changes and mainly the value of the new currents in certain fields of the human activity, the Law of Public Purchases, to appreciate the new currents, suits then to present the current panorama; more the related with the execution of works, the acquisition of goods and the benefit of services that complete the environment of the Law, being excluded the special contracts of régime. With the help of specific quantities the recruiting settles down, being carried out the bids of conformity to the Public Portal of Purchases in validity, a system of guarantees, as well as him with respect to the capacities and special inabilities or generals to hire, or about the nullity of the recruitings, on the requirements, it forms and registration of contracts, about the readjustments of prices; on the receptions; it has more than enough complementary and additional contracts; it has more than enough termination of contracts; contractors' registration and about the responsibilities of those who intervene in the recruiting processes. So soon you public the new Law of Public Purchases, was thought that with new and fairer and more equal rules for one and the other field in other words that you/they represented everything when it could be legislated in this respect; however, it lacks a lot to consider and to contemplate in the new laws, that that in turn produces the multiplicity of consultations to the General Attorney's office of the State, in spite of that which all the problems were not overcome. The immediate effect was the difficulties that affected to the contracting entities and the contractors, divergences that were taken to the tribunals of justice, and other times in some cases the abandonment of the works that was the most immediate solution to the contractor's approach was; in everything, I marry, it has been the State and the community in general the more harmed with the unconcluded and abandoned works and with the unsuccessful investments; in front of this reality, the necessity was imposed of revising the field of the public recruiting and the elaboration of legal new bodies that not only viabilizan the recruitings, but rather they make them more dynamic and more transparent, so much more if the country has entered in the stage of the modernization. Corresponding to this yearning, it must pick up the new currents on the Public Recruiting, and that they are translated in reforming the recruiting régime, propitiating the application of the administrative modern right, the collective interest, the artificial security and the legality as well as the biggest transparency, efficiency and competitiveness, upgrading the juridical effective mark and to contribute to the harmonization among the administration and those administered, between the public interest and the private action, between the Public Right and the norms of the Private Right.